Analysis of Self-Medication Patterns in South Surabaya Community in the Era of the COVID-19 Pandemic - Wening Sari; Della Nanda Shafa Nabilah (Nusantara Science and Technology Proceedings)
Background: Indonesia implemented a large-scale social restriction policy throughout the COVID-19 pandemic. Hospitals and alternative health care facilities are places with a high risk of COVID-19 transmission. The general public is suggested to limit visits to health facilities unless it is an emergency. Supported this, we hypothesize that people prefer to self-medicate to take care of relatively mild health complaints at home. This study aims to analyze the pattern of self-medication within the community in the era of the COVID-19 pandemic. Methods: A cross-sectional survey was conducted on 110 residents of South Surabaya with a structured questionnaire during the COVID-19 outbreak in December 2021, to observe patterns and factors that influence people's decisions to take self-medication before and during the COVID-19 pandemic era. Results: As several as 40% of respondents had self-medication before the COVID-19 pandemic, while the prevalence of self-medication within the thick of the COVID-19 outbreak was 57.3%. The most reasons for self-medication are the concern of reaching the hospital will be being exposed to COVID-19 (67.3%), the sickness is not severe enough, compatible with the previous medication, and more efficient. The community's advantages of self-medication are that it is faster to treat (41%) and cheaper (21.8%). Conclusions: The study revealed that there was an increase in the number of respondents who did self-medication during the COVID-19 pandemic with the main reason being fear of going to the public health center or hospital.